Disentangling the South American “Ceratomontia”: new genus, new combinations, and new species (Opiliones: Laniatores: Triaenonychidae) - Porto, Willians; Iglesias, Patricia P.; Pérez-González, Abel (Zootaxa, 2025)
Previous phylogenetic studies using morphological or molecular characters failed to recover the transcontinental triaenonychid genus Ceratomontia Roewer, 1915, as monophyletic, and pointed out the necessity to erect a new genus for the new world representatives. In this work we address this taxonomic claim and the genus Maurymontia gen. nov. is described to include the South American species. In addition to the proposed new combinations, we also provide a detailed redescription and illustrations for all the previously known species: Maurymontia argentina (Canals, 1939) comb. nov., Maurymontia brasiliana (Maury, 1999) comb. nov., Maurymontia centralis (Maury & Roig Alsina, 1985) comb. nov. and Maurymontia mendocina (Maury & Roig Alsina, 1985) comb. nov. Furthermore, we increase the genus composition with the description of three new species from Argentina: Maurymontia grismadoi sp. nov., Maurymontia mborore sp. nov. and Maurymontia trescerros sp. nov. Finally, we discuss some points regarding geographic distribution, the external and genital morphology.